The Role of Parents During The Covid-19 Pandemic: Description Of Child Development Activities - Yenti Juniarti; Fitriana; Lia Ricka Pratama (STKIP Muhammadiyah Kuningan, 2022)
The problem of this research was taken from the anxiety of parents in their children during the pandemic, in which parents who were previously busy with their respective affairs, and then turned into the responsibility of taking care of children's learning. This article aims to find out how the role of parents in carrying out child development activities during the COVID-19 pandemic. This research method uses a qualitative, case study approach, while the research steps using Miles & Huberman are data collection, data reduction, data presentation and conclusion drawing. The data mining was carried out by observation and in-depth interviews with 4 heads of families, 3 fathers and 5 mothers. The results show that child development activities during the pandemic are certainly different from usual because they are carried out from home. However, it does not reduce the activities of the five aspects of child development. watching television, communicating, role playing, loving animals, watering flowers, playing puzzles, writing, counting, and other activities to help parents. This makes the development of religious and moral values, cognitive, language, social emotional and physical motor able to develop optimally without being left behind in any aspect stimulated during the COVID-19 pandemic. A timetable for children to carry out various activities at home so that aspects of children's development can develop optimally during learning activities from home.